An adaptive approach for vehicle suspension system control in presence of uncertainty and unknown actuator time delay. Issue 1 (1st January 2021) - Fazeli, Samaneh; Moarefianpur, Ali
Abstract : This paper presents an adaptive approach for controlling the nonlinear vehicle suspension system in the presence of unknown delay and limited disturbance. All three factors present in the quarter vehicle suspension model including uncertainty, disturbance and input delay are limited but unknown. This paper dealings a nonlinear model to describe more accurately the behaviour of the suspension and the controller design. To prove stability in the Lyapunov concept, the proposed control method is a combination of backstepping and adaptive approaches. The results of the simulation confirm better active suspension performance regardless of the unknown time delay, disturbances and uncertainty in the nonlinear model.